Central Asian Rodents as Model Animals for Leishmania major and Leishmania donovani Research - Vojtkova, Barbora; Spitzova, Tatiana; Votypka, Jan; Lestinova, Tereza; Kominkova, Iveta; Hajkova, Michaela; Santos-Mateus, David; Miles, Michael A; Volf, Petr; Sadlova, Jovana (Microorganisms, 2020)
The clinical manifestation of leishmaniases depends on parasite species, host genetic background, and immune response. Manifestations of human leishmaniases are highly variable, ranging from self-healing skin lesions to fatal visceral disease. The scope of standard model hosts is insufficient to mimic well the wide disease spectrum, which compels the introduction of new model animals for leishmaniasis research. In this article, we study the susceptibility of three Asian rodent species (Cricetulus griseus, Lagurus lagurus, and Phodopus sungorus) to Leishmania major and L. donovani. The external manifestation of the disease, distribution, as well as load of parasites and infectiousness to natural sand fly vectors, were compared with standard models, BALB/c mice and Mesocricetus auratus. No significant differences were found in disease outcomes in animals inoculated with sand fly- or culture-derived parasites. All Asian rodent species were highly susceptible to L. major. Phodopus sungorus showed the non-healing phenotype with the progressive growth of ulcerative lesions and massive parasite loads. Lagurus lagurus and C. griseus represented the healing phenotype, the latter with high infectiousness to vectors, mimicking best the character of natural reservoir hosts. Both, L. lagurus and C. griseus were also highly susceptible to L. donovani, having wider parasite distribution and higher parasite loads and infectiousness than standard model animals.
Keywords: Cricetulus griseus; Phlebotomus; infectiousness; model animals; visceral leishmaniasis; xenodiagnosis; sand fly; Phodopus sungorus; Lagurus lagurus; cutaneous leishmaniasis